2018
DOI: 10.1155/2018/5258797
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Associated Differential mRNA Expression of Cytokines and Its Regulation by Sex Steroids in Different Brain Regions in aPlasmodium bergheiANKA Model of Cerebral Malaria

Abstract: Cerebral malaria (CM) is the major complication associated with death in malaria patients, and its pathogenesis is associated with excessive proinflammatory cytokine production. Notably, the severity and mortality of natural infections with Plasmodium are higher in males than females, suggesting that sexual hormones influence both the pathogenesis of and immune response in CM. However, no studies on inflammation mediators in the brains of both sexes have been reported. In this work, the mRNA expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Immune cells modulate immunity by secreting cytokines. In this work, we detected that infection with P. berghei ANKA increased the concentrations of IFN-γ and TNF-α, which corroborates what has been previously described [ 55 ]. In addition, DHEA administration decreased the concentration of IFN-γ in intact infected females compared to intact infected males, resulting in a sex-associated pattern.…”
Section: Discussionsupporting
confidence: 92%
“…Immune cells modulate immunity by secreting cytokines. In this work, we detected that infection with P. berghei ANKA increased the concentrations of IFN-γ and TNF-α, which corroborates what has been previously described [ 55 ]. In addition, DHEA administration decreased the concentration of IFN-γ in intact infected females compared to intact infected males, resulting in a sex-associated pattern.…”
Section: Discussionsupporting
confidence: 92%
“…It exhibits a marked sexual dimorphism, with males showing higher parasitaemia, symptom severity and mortality than females. Sex hormones are involved in the sexual dimorphism of the immune response in malaria ( Lopes et al., 2016 ; Legorreta-Herrera et al., 2018 ; Cervantes-Candelas et al., 2021 ); oestrogens induce immunocompetence. In contrast, testosterone, the primary male hormone, generates immunosuppression ( Wichmann et al., 1996 ; Wunderlich et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous works from different groups have shown that OVX induces neuroinflammation (overproduction of inflammatory cytokines and glial activation in CNS) and/or memory decline, depression-like behaviors in mice, [45][46][47][48][49][50][51][52][53] and in rats. [54][55][56][57][58] Consistently, in the present work we found that chronic pain and memory/emotional deficits were associated with neuroinflammation in OVX and aged female mice.…”
Section: Discussionmentioning
confidence: 99%